1997
DOI: 10.1007/s004410050885
|View full text |Cite
|
Sign up to set email alerts
|

Origin of metazoan adhesion molecules and adhesion receptors as deduced from cDNA analyses in the marine sponge Geodia cydonium : a review

Abstract: The phylogenetic relationships of the kingdom Animalia (Metazoa) have long been questioned. Whether the lowest eukaryotic multicellular organisms, the metazoan phylum Porifera (sponges), independently evolved multicellularity from a separate protist lineage (polyphyly of animals) or whether they were derived from the same protist group as the other animal phyla (monophyly) remains unclear. Analyses of the genes that are typical for multicellularity, e.g. those coding for adhesion molecules (galectin) and adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(53 citation statements)
references
References 72 publications
(67 reference statements)
0
53
0
Order By: Relevance
“…The transition from Protozoa to Metazoa dates back 600-1000 million years ago (reviewed in : Müller 1997;Nikoh et al 1997). It has been proposed that oxygen level, temperature, and seawater chemistry played major roles in the evolution from Protozoa to Metazoa (Seilacher 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The transition from Protozoa to Metazoa dates back 600-1000 million years ago (reviewed in : Müller 1997;Nikoh et al 1997). It has been proposed that oxygen level, temperature, and seawater chemistry played major roles in the evolution from Protozoa to Metazoa (Seilacher 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The sponge MTL represents a tandem duplicated polypeptide composed of 2 parts which are highly related to metazoan MTs. This finding is not too surprising in view of our earlier studies, which revealed that the domain composition and the degree of domain duplication in the sponge genome is unusually complex in comparison to other metazoan phyla (reviewed in Miiller 1997Miiller , 1998. The second distinction between the sponge MTL and the metazoan MTs, which are usually constitutively expressed, especially in tissue undergoing growth and differentiation (Brady et al 19821, is the fact that the sponge MTL is an inducible protein.…”
Section: Discussionmentioning
confidence: 78%
“…There is only one report in the literature that assigns a definitive role for a sponge lectin, the Geodia cydonium lectin, which may act as a bridge linking the aggregation factor to cells (39). G. cydonium is the most characterized sponge lectin to date (6, 33, 40 -42), and it has been included recently (3,(43)(44)(45)(46) in the Galectins family (47)(48)(49)(50)(51)(52), based on DNA sequence homology. The Galectins are soluble proteins with a conserved S-type domain, which share the ability to bind ␤-galactosides in polylactosamine units.…”
Section: Discussionmentioning
confidence: 99%